2021
DOI: 10.3233/hsm-200913
|View full text |Cite
|
Sign up to set email alerts
|

Organic consumption through ICT: A moderated mediation model of consumer attitude and perceived irritation

Abstract: BACKGROUND: The proliferation of ICT has transformed customers’ buying patterns. The organic consumption patterns based on online consumers’ reviews were reviewed through moderated mediation model. This research paper examines the mediating role of consumer attitude in the relationship between online consumers’ reviews and organic consumption. It further examines, if perceived irritation moderates this effect. METHODS: Data were collected from 287 respondents who were experienced in online buying of organic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, given thatonline shopping has gained wide acceptance and consumers more efficient and goaldirected following their proclivity with the consumption of information and interactions online (Tariq &Tanveer, 2021), the extent online advertising fulfils these goals have been scarcely investigated. Previous research showed that consumer surf the web for entertainment value, information involvement, interaction, and irritation (Luo, 2002;Ko, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given thatonline shopping has gained wide acceptance and consumers more efficient and goaldirected following their proclivity with the consumption of information and interactions online (Tariq &Tanveer, 2021), the extent online advertising fulfils these goals have been scarcely investigated. Previous research showed that consumer surf the web for entertainment value, information involvement, interaction, and irritation (Luo, 2002;Ko, 2002).…”
Section: Introductionmentioning
confidence: 99%